2011
DOI: 10.3945/ajcn.110.002220
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of iron and zinc supplementation during infancy on cognitive function at 9 y of age in northeast Thai children: a follow-up study

Abstract: Supplementation with iron or zinc or both during infancy does not lead to long-term cognitive improvement in 9-y-old children. This trial was registered at clinicaltrials.gov as NCT00824304.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 33 publications
3
39
1
Order By: Relevance
“…Two follow-up studies of school-age children (age 7–9 years) who received iron + zinc supplementation during infancy showed no long term effects on cognition [40,41]. In one study from Thailand, iron + zinc supplementation was given for 6 months beginning at 4–6 months of age and cognitive functioning was measured with global measures and school performance [40].…”
Section: Iron Supplementation/fortificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two follow-up studies of school-age children (age 7–9 years) who received iron + zinc supplementation during infancy showed no long term effects on cognition [40,41]. In one study from Thailand, iron + zinc supplementation was given for 6 months beginning at 4–6 months of age and cognitive functioning was measured with global measures and school performance [40].…”
Section: Iron Supplementation/fortificationmentioning
confidence: 99%
“…In one study from Thailand, iron + zinc supplementation was given for 6 months beginning at 4–6 months of age and cognitive functioning was measured with global measures and school performance [40]. In the other study from Nepal, iron-folic acid or zinc was given to 12–36 month old children who had participated in an antenatal supplementation trial of iron or zinc, separately, and in combination [41].…”
Section: Iron Supplementation/fortificationmentioning
confidence: 99%
“…93,94 Therapeutic responses to Zn supplementation have been observed in multiple infectious diseases 95 and recently, a number of controlled intervention trials have been conducted to unveil the impact of Zn supplementation on cognitive performance and other health outcomes in children. A metaanalysis of 33 randomized controlled trials on Zn supplementation in children found a large effect on height and weight increments, 96 while the evidence regarding the effects of Zn on cognitive function in children lacks a clear consensus [97][98][99] which may be due to the dependency on further micronutrients, the life period and degree of deficiency, or the methodological features mentioned above. On the other hand, high Zn intake interferes with the intestinal absorption of copper and can induce a copper deficiency 92 (and vice versa 100 ), which is made use of in the utilization of Zn for the treatment of Wilson's disease.…”
Section: Zinc Deficiency and Healthmentioning
confidence: 99%
“…Children were followed up at the age of 9 years, when the authors found no differences overall or in any domain of the Wechsler Intelligence Scale for Children-III between the groups, or in the Raven's Colored Progressive Matrices score. Moreover, no differences in school performance in any subject (Thai, English, Mathematics, or Science) were observed [49] . Collectively, these studies do not support the hypothesis that even quite sustained courses of iron supplementation in young children benefit cognitive performance in the long term.…”
Section: Does Supplementation In Preschool Children Improve Short-termentioning
confidence: 99%